Given:
Two intercept points be (-2,0) and (4,0) and passing through the point (1,-27).
Let the equation of parabola be
![y=ax^2+bx+c](https://img.qammunity.org/2023/formulas/mathematics/high-school/g7mvpjunjwe6qob7ddy7l4f0glbtdi9gci.png)
Substituting the points we get,
![\begin{gathered} 4a-2b+c=0\ldots\text{ (1)} \\ 16a+4b+c=0\ldots\text{ (2)} \\ a+b+c=-27\ldots\text{ (3)} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/lfn76g5dq4kwun73ilmaifapvmqsxb37l5.png)
Solving (1) and (2) we get,
![\begin{gathered} 12a+6b=0 \\ 2a+b=0\ldots\text{ (4)} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/yrx4pzpuh9dehajzrayxe7pv91t97kuv5w.png)
Solving (2) and (3) we get,
![\begin{gathered} 15a+3b=27 \\ 5a+b=9\ldots\text{ (5)} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/vukv72rz8gxxy0yev28piyyjx65hfbit35.png)
Solving (4) and (5)
![\begin{gathered} 3a=9 \\ a=3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ro9cgy2lh36vbtyuyrf1hvfarkl0l6f686.png)
Substituting a=3 in (4)
![\begin{gathered} 2(3)+b=0 \\ b=-6 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/mv0r1wegtb43y5nxbp1bx606tcuvuvk9tb.png)
Substitute a=3 & b=-6 in (1)
![\begin{gathered} 3-6+c=-27 \\ -3+c=-27 \\ c=-24 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/eypqaip3n6gi8yq9c6ie78tewe93ezzuoz.png)
Equation of parabola is
![y=3x^2-6x-24](https://img.qammunity.org/2023/formulas/mathematics/college/7p49wlbd4dbqz0tho4bbe5gie73lx8g6yp.png)